Improving The Principles of Treatment Of Autoimmune Hepatitis. - Tairova G.B. (Genius Journals, 2023)
This chronic autoimmune liver disease with inflammation of liver cells with the description of unknown etiology. The disease occurs in people of different ages and for many years can be hidden. During the disease, liver failure, and death sorosis can be observed. Autoimmune hepatitis is one of the rare types of liver diseases in the country, and about 2 percent of the chronic liver diseases 2: Occurs at a ratio of 100000. Available in three types of this disease occurring in women. The 1-category of autoimmune hepatitis 70% of patients make up for it. The treatment of the disease in long-term corticosteroid therapy is carried out. As a result of cirrhosis in patients with this disease only to the last stage of a baking treatment is liver transplantation. Autoimmune hepatitis (AIH) is conducted under the control of the disease in clinical therapeutic research - with corticostroids is effective for the treatment of liver disease, which is the show that first. Nevertheless, AIH is still a big problem remains a diagnostic and therapeutic get up to the present day. There are two main causes of this problem. First, let the AIH is that the disease is relatively rare. Secondly, heterogeny very sick.
Keywords: disease; problem; therapeutic; heterogeny